2007
DOI: 10.1007/s11606-007-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Different Interpreting Methods: A Randomized Controlled Trial

Abstract: BACKGROUND: Growth of the foreign-born population in the U.S. has led to increasing numbers of limitedEnglish-proficient (LEP) patients. Innovative medical interpreting strategies, including remote simultaneous medical interpreting (RSMI), have arisen to address the language barrier. This study evaluates the impact of interpreting method on patient satisfaction.METHODS: 1,276 English-, Spanish-, Mandarin-, and Cantonese-speaking patients attending the primary care clinic and emergency department of a large New… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 29 publications
(25 reference statements)
1
65
1
4
Order By: Relevance
“…33,34 Other remote interpretation methods, such as video or remote simultaneous medical interpreting, demonstrate promise in increasing interpreter use and patient satisfaction and may be an important way to increase interpreter use among pediatricians. 35,36 To date, evaluation of use of these interpretation methods has been in large, urban settings; more research is needed on how well remote interpretation methods can address financial and resource barriers to interpreter use in rural or small practices. There are also few examples of how practices or hospitals may collaborate to maximize interpreter availability and contain costs, which may be especially important for small or more rural practices.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Other remote interpretation methods, such as video or remote simultaneous medical interpreting, demonstrate promise in increasing interpreter use and patient satisfaction and may be an important way to increase interpreter use among pediatricians. 35,36 To date, evaluation of use of these interpretation methods has been in large, urban settings; more research is needed on how well remote interpretation methods can address financial and resource barriers to interpreter use in rural or small practices. There are also few examples of how practices or hospitals may collaborate to maximize interpreter availability and contain costs, which may be especially important for small or more rural practices.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that remote telephone or video conferencing modes are as effective as in-person interpretation as measured by communication quality and patient satisfaction. [34][35][36][37] Use of these non in-person methods should be encouraged in the hospital setting, where in-person interpretation may not be readily available throughout the 24-hour hospital continuum of care.…”
Section: Mutltivariable Analyses Of Hospital Outcomesmentioning
confidence: 99%
“…In one study, communication problems contributed to adverse events at a much higher rate among LEP patients (52.4%) than English speakers (35.9%), with 49.1% of adverse events rising to the level of clinical significance in LEP populations, compared to 29.5% in English-speaking populations. 3 Many studies have shown that LEP patients tend to have lower rates of preventive screening and higher rates of hospitalization and drug complications 2,3,9,[11][12][13][14][15] . Lack of discussion and poor understanding of treatment plans, including medication side effects, are likely reasons for these concerning rates, as such factors can lead to patient dissatisfaction and reduce adherence to physician recommendations [16][17][18] .…”
mentioning
confidence: 99%